Inclusive Communication: Unveiling Disabilities, Building Harmony in Diversity - Nurdin, Ali (Proceedings of International Conference on Da'wa and Communication, 2023)
The problems of people with disabilities are part of the global humanitarian problem. People with disabilities have limitations in social communication with the surrounding environment. The aim of this research is to explain inclusive communication for people with disabilities in creating harmony in social life. The research used a literature review type by reviewing 50 research articles on disability. The research results found that there are three categories of disabilities, namely physical, sensory, and intellectual disabilities. Physical disabilities include congenital paralysis, amputation, or similar. Sensory disabilities include blindness, deafness, and inability to speak. Intellectual disabilities include autism or syndrome, depression, anxiety disorders, and schizophrenia. These limitations that people with disabilities have give rise to social pressure, inequality and even social discrimination. Inclusive communication plays a role in bridging the gap between people with disabilities and their social environment. Inclusive communication brings equality in social communication and supports the point of view of people with disabilities. Inclusive communication maintains self-openness for people with disabilities with empathy without prejudice, tolerance without intervention, and respect without degrading them.